SURONO'S CROSS-STYLED CREATION IN THE SHADOW PUPPET PERFORMANCE - Rhama, Chatur; Harpawati, Tatik (ARTISTIC : International Journal of Creation and Innovation, 2023)
Surono Gondo Taruno's shadow puppet (wayang kulit) performance has a distinctive cross-style, making him a famous puppeteer in East Java. Accordingly, this discussion seeks to answer the question, "What is the cross-style of Surono's wayang figures in the Wahyu Wijaya Kusuma play? This discussion uses a qualitative method with Sunardi and Umar Kayam's cross-styled approach. Observational and interview-based were analyzed descriptively and qualitatively. The study results indicate that Surono's performance uses a cross-styled approach between the Surakarta style as the dominant style and the East Java and the Yogyakarta styles as the supporters. Surono's cross-style has made his performance attractive to contemporary spectators.